HUMAN FOLLOWING ON ROS FRAMEWORK A MOBILE ROBOT - Gigih Priyandoko; Choi Kah Wei; Muhammad Sobirin Hendriyawan Achmad (SINERGI, 2018)
Service mobile robot is playing a more critical role in today's society as more people such as a disabled person or the elderly are in need of mobile robot assistance. An autonomous person following ability shows great importance to the overall role of service mobile robot in assisting human. The objective of this paper focuses on developing a robot follow a person. The robot is equipped with the necessary sensors such as a Microsoft Kinect sensor and a Hokuyo laser sensor. Four suitable tracking methods are introduced in this project which is implemented and tested on the person following algorithm. The tracking methods implemented are face detection, leg detection, color detection and person blob detection. All of the algorithms implementations in this project is performed using Robot Operating System (ROS). The result showed that the mobile robot could track and follow the target person based on the person movement.